Empirical Comparision Banking Service and Dental Service in using Firm Resources to Enhance Customer Loyalty - Nguyen Tran Cam Linh; Tran Duc Anh (International Journal of Supply Chain Management, 2020)
In the past, Good - Dominant logic said that customer could not evaluate the enterprise resource. But nowadays, according to Service - Dominant logic, the customer can determine the enterprise resource through the process of using service to decide which of the supplier to work. This study investigates the relationship between enterprise resources and service value; and the relationship between service value and customer loyalty by using qualitative research methods and quantitative research methods. Results show a positive and direct impact of supplier resources on service value; similar results to the effects of service value on customer loyalty. Base on that results, this research gives some solutions and recommendations for each kind of services to improve customer loyalty.